2017
DOI: 10.1002/2017gl073565
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric deposition of glacial iron in the Gulf of Alaska impacted by the position of the Aleutian Low

Abstract: Our understanding of glacial flour dust storm delivery of iron to the Gulf of Alaska (GoA) is limited. Here we interpret concurrent time series satellite, meteorological, and aerosol geochemical data from the GoA to examine how interannual variability in regional weather patterns impacts offshore aerosol glacial Fe deposition. In 2011, when a northerly Aleutian Low (AL) was persistent during fall, dust emission was suppressed and highly intermittent due to prevalent wet conditions, low winds, and a deep early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 34 publications
4
51
0
Order By: Relevance
“…The FeA and FeD contents in Icelandic dust are similar to what were measured by Raiswell et al (2016) in ice-hosted sediments: 0.03 wt %-0.2 wt % for FeA and 0.04 wt %-0.7 wt % for FeD. Previous research investigated the initial fractional Fe solubility of dust from glacial sediments in the Copper River valley, an important source of Fe for the Gulf of Alaska, which is Fe limited (Crusius et al, 2011;Schroth et al, 2009Schroth et al, , 2017. Glacial dust and sediments showed high initial fractional Fe solubility, which was associated with a low degree of chemical weathering (Schroth et al, 2009(Schroth et al, , 2017.…”
Section: Factors Controlling Fe Solubility In Icelandic Dustsupporting
confidence: 67%
See 2 more Smart Citations
“…The FeA and FeD contents in Icelandic dust are similar to what were measured by Raiswell et al (2016) in ice-hosted sediments: 0.03 wt %-0.2 wt % for FeA and 0.04 wt %-0.7 wt % for FeD. Previous research investigated the initial fractional Fe solubility of dust from glacial sediments in the Copper River valley, an important source of Fe for the Gulf of Alaska, which is Fe limited (Crusius et al, 2011;Schroth et al, 2009Schroth et al, , 2017. Glacial dust and sediments showed high initial fractional Fe solubility, which was associated with a low degree of chemical weathering (Schroth et al, 2009(Schroth et al, , 2017.…”
Section: Factors Controlling Fe Solubility In Icelandic Dustsupporting
confidence: 67%
“…The imaginary part of the complex refractive index (k), responsible for absorption, was 0.01 (λ = 647 nm), which is around 1 order of magnitude higher than the average values for natural dust from the Sahel (0.002, λ = 660 nm) and northern-Africa-Sahara and eastern Asia (0.001, λ = 660 nm) (Di Biagio et al, 2019). In the shortwave spectrum, the k values reported in literature for volcanic ash from Iceland range from around 0.0001 to 0.02 (Ball et al, 2015;Bukowiecki et al, 2011;Derimian et al, 2012;Hervo et al, 2012;Reed et al, 2017;Rocha-Lima et al, 2014;Schumann et al, 2011;Toledano et al, 2012;Vogel et al, 2017;Weinzierl et al, 2012), which makes it difficult to evaluate the absorption properties of volcanic dust.…”
Section: Implications For the Soluble Fe Deposition To The Oceanmentioning
confidence: 69%
See 1 more Smart Citation
“…Shoenfelt et al [116] recently proposed that nutrients contained in dust originating from glacigenic sources at high latitudes show higher levels of bioavailability and thus a stronger potential to influence on the oceans bioproductivity and thus the global carbon cycle. Strong interannual variability in dust storm occurrence and thus dust deposition fluxes lead to significant interannual variability in iron deposition fluxes as shown by Schroth et al [117] for the Gulf of Alaska.…”
Section: Blowing With the Wind: Atmospheric Transport Of Mineral Dustmentioning
confidence: 85%
“…Fe-limited. Dust storms emanating from glacierized river valleys along the northern GoA coastline have been shown to transport dust hundreds of kilometers beyond the shelf break in the late autumn [e.g., Crusius et al, 2011;Schroth et al, 2017], while dust from the Gobi and other deserts have been reported in this region in the spring [Zdanowicz et al, 2006;Yasunari et al, 2007]. The annual dust flux to the eastern subarctic North Pacific ocean has been estimated by several different independent methods to be approximately 1 g m À2 a À1 (Table 2).…”
Section: 1002/2016gb005493mentioning
confidence: 99%